Long-term outcomes after facial allotransplantation: systematic review of the literature - Tchiloemba, Bianief; Kauke-Navarro, Martin; Haug, Valentin; Abdulrazzak, Obada; Safi, Ali-Farid; Kollár, Branislav; Pomahac, Bohdan (Transplantation, 2021)
Export - Background. Facial vascularized composite allotransplantation (fVCA) represents a reconstructive approach that enables superior improvements in functional and esthetic restoration compared with conventional craniomaxillofacial reconstruction. Outcome reports of fVCA are usually limited to short-term follow-up or single-center experiences. We merge scientific literature on reported long-term outcome data to better define the risks and benefits of fVCA. - Methods. - We conducted a systematic review of PubMed/MEDLINE databases in accordance with PRISMA guidelines. English full-text articles providing data on at least 1 unique fVCA patient, with ≥3 years follow-up, were included. - Results. - The search yielded 1812 articles, of which 28 were ultimately included. We retrieved data on 23 fVCA patients with mean follow-up of 5.3 years. More than half of the patients showed improved quality of life, eating, speech, and motor and sensory function following fVCA. On average, the patients had 1 acute cell-mediated rejection and infectious episode per year. The incidence rates of acute rejection and infectious complications were high within first-year posttransplant but declined thereafter. Sixty-five percent of the patients developed at least 1 neoplastic or metabolic complication after transplantation. Chronic vascular rejection was confirmed in 2 patients, leading to allograft loss after 8 and 9 years. Two patient deaths occurred 3.5 and 10.5 years after transplant due to suicide and lung cancer, respectively. - Conclusions. - Allograft functionality and improvements in quality of life suggest a positive risk-benefit ratio for fVCA. Recurrent acute rejection episodes, chronic rejection, immunosuppression-related complications, and heterogeneity in outcome reporting present ongoing challenges in this field.
Gesehen am 13.10.2021